Pelatihan Pengelolaan Sayuran Hidroponik untuk Peningkatan Kesejahteraan Warga Kec. Rappocini, Makassar-Sulawesi Selatan: Pengabdian - Al Kausar; Aminuddin Hamdat; Ceskakusumadewi Baharuddin; Sulkipli; A. Dwie Mochammad Abduh (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The hydroponic vegetable cultivation training program in RW 03, Bumi Permata Hijau Complex, Rappocini District, Makassar, aims to improve community welfare through the utilization of limited land and water resources. The implementation methods included technical cultivation training, economic assistance, marketing of harvests, and strengthening of environmental community engagement. The results showed that 80% of participants successfully built independent hydroponic modules and gained increased knowledge and skills in cultivation. Economically, residents were able to generate additional income ranging from IDR 1,656,000 to IDR 1,840,000 per year per module. Furthermore, the environment became cleaner and greener due to the active involvement of residents in hydroponic farming. This success demonstrates that hydroponic technology can be a sustainable solution for enhancing economic well-being, environmental preservation, and community-based empowerment.